2022
DOI: 10.1155/2022/7053521
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Gene Expression in Menstrual Blood-Derived Stromal Cells between Endometriosis and Healthy Women

Abstract: Background. Research into the pathogenesis of endometriosis would substantially promote its effective treatment and early diagnosis. Currently, accumulating evidence has shed light on the importance of endometrial stem cells within the menstrual blood which are involved in the establishment and progression of endometriotic lesions in a retrograde manner. Objectives. We aimed to identify the differences in some genes’ expression between menstrual blood-derived mesenchymal stem cells (MenSCs) isolated from endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
(72 reference statements)
1
20
0
Order By: Relevance
“…The expression of inflammatory genes, such as IL-1β , IL-6 , IL-8 , and NF-κB , and that of stemness genes, including SRY-Box Transcription Factor 2 ( SOX2 ) and Spalt Like Transcription Factor 4 ( SALL4 ), is also highly elevated in endometriotic MSCs compared with normal MSCs. Furthermore, endometriotic MSCs express higher levels of VEGF than normal MSCs [ 92 ]. Ectopic MSCs exhibit more aggressive migration and invasion characteristics than eutopic MSCs in vivo and in vitro [ 91 ].…”
Section: Dysregulation Of Interferon Signaling In Endometriosismentioning
confidence: 99%
“…The expression of inflammatory genes, such as IL-1β , IL-6 , IL-8 , and NF-κB , and that of stemness genes, including SRY-Box Transcription Factor 2 ( SOX2 ) and Spalt Like Transcription Factor 4 ( SALL4 ), is also highly elevated in endometriotic MSCs compared with normal MSCs. Furthermore, endometriotic MSCs express higher levels of VEGF than normal MSCs [ 92 ]. Ectopic MSCs exhibit more aggressive migration and invasion characteristics than eutopic MSCs in vivo and in vitro [ 91 ].…”
Section: Dysregulation Of Interferon Signaling In Endometriosismentioning
confidence: 99%
“…Consequently, they are considered a promising tool for regenerative medicine [ 1 , 2 , 3 ]. Due to the varied potential of clinical applications combined with no ethical dilemma, MenSCs have gained prominence in the scientific community since their discovery in 2007 [ 4 ] in different gynecological diseases [ 5 ] and, therefore, in the context of endometriosis [ 6 , 7 , 8 , 9 ]. Particular emphasis has been given to the different functionalities of these progenitor cells regarding the etiopathogenic mechanism [ 8 ] and reproductive aspects of endometriosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new contemporary study 28 indicates that E-MenSCs had higher expression of Cyclin D1 (a cell cycle-related gene), MMP2 and MMP9 (migration- and invasion-related genes), and SOX2 and SALL4 (stemness genes) genes compared with H-MenSCs. In our research, we demonstrated that implanting cell density truly played a role in cell proliferation ability: the proliferation ability of H-MenSCs (1 × 10 5 cells/mL) surpassed E-MenSCs with lower density (5 × 10 4 cells/mL), while E-MenSCs are still superior to H-MenSCs at the same lower density (5 × 10 4 cells/mL).…”
Section: Discussionmentioning
confidence: 99%